The Role of Information Management in Enhancing Organizational Resilience - Lansonia, April; Austin, Matthias (Pandawan, 2024)
In the face of constant change and unprecedented challenges, organizations are compelled to cultivate resilience. This study focuses on the pivotal role of information management in fortifying organizational resilience, recognizing the imperative for a strategic approach to information handling in today's dynamic landscape. Employing a quantitative research approach, the study aims to comprehensively understand the nuanced relationships between information management and organizational resilience. By capturing empirical data, quantitative methodologies enable statistical analysis to unveil patterns and trends, shedding light on the presence, strength, and direction of the relationship between information management practices and resilience. The study's contributions extend to both academic and practical realms. Academic researchers gain insights into how strategic information management influences organizational resilience, informing the development of new theories. Practitioners can leverage actionable insights to guide strategic decision-making, enhancing organizational adaptation and thriving. Whether through improving data security, enhancing information accessibility, or refining data management, organizations can fortify their foundations in the ever-evolving business landscape. In conclusion, this study offers practical implications for organizational leaders, emphasizing the pivotal role of strategic information management in not only surviving but thriving amid disruptions. The synthesis of empirical evidence and theoretical insights positions this research as a valuable resource for those dedicated to bolstering organizational resilience in the face of dynamic uncertainties.